2018
DOI: 10.1148/radiol.2018170425
|View full text |Cite
|
Sign up to set email alerts
|

Validation of PI-RADS Version 2 in Transition Zone Lesions for the Detection of Prostate Cancer

Abstract: Purpose To determine the association between Prostate Imaging Reporting and Data System (PI-RADS) version 2 scores and prostate cancer (PCa) in a cohort of patients undergoing biopsy of transition zone (TZ) lesions. Materials and Methods A total of 634 TZ lesions in 457 patients were identified from a prospectively maintained database of consecutive patients undergoing prostate magnetic resonance imaging. Prostate lesions were retrospectively categorized with the PI-RADS version 2 system by two readers in cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 22 publications
2
42
0
7
Order By: Relevance
“…The second subgroup analysis evaluated TZ PCa to only stromal BPH nodules for lesions that measured <15 mm in size (eg, PI‐RADS v2 assessment category 4 lesions), which have a much lower yield for clinically significant cancer at targeted biopsy compared with lesions measuring >15 mm in size . There was no difference comparing size of <15 mm TZ tumors and stromal BPH nodules (13 ± 2 mm vs. 11 ± 2 mm, P = 0.78).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The second subgroup analysis evaluated TZ PCa to only stromal BPH nodules for lesions that measured <15 mm in size (eg, PI‐RADS v2 assessment category 4 lesions), which have a much lower yield for clinically significant cancer at targeted biopsy compared with lesions measuring >15 mm in size . There was no difference comparing size of <15 mm TZ tumors and stromal BPH nodules (13 ± 2 mm vs. 11 ± 2 mm, P = 0.78).…”
Section: Resultsmentioning
confidence: 99%
“…We have noted that specific features of TZ PCa described in PI‐RADS v2 including lenticular shape, a noncircumscribed (blurred, indistinct, irregular, or spiculated) border and the absence of a complete hypointense rim are limited when assessing smaller lesions in the TZ, where these features may be absent or difficult to apply subjectively. This was confirmed by Thai et al, who showed a substantial disparity in the detection of significant cancer when comparing lesions measuring over or under 15 mm in size . Furthermore, the described imaging findings of TZ cancer on T 2 W and DWI in PI‐RADS v2 are subjective and may not be entirely reproducible …”
mentioning
confidence: 76%
See 3 more Smart Citations